Pendidikan Karakter Anak Usia Dini Melalui Mainan Edukatif Amigurumi Berbasis Budaya Lokal - Ni Wayan Satiani Pradnya Paramita (Jurnal Pendidikan dan Penciptaan Seni, 2021)
Character building needs to be given as early as possible. Educational toys can be a medium for character building, but it is still rare to find educational toys that have local cultural values. Most of these educational toys refer to popular toys that are oriented towards Western culture. This condition needs to be balanced with the creation of educational toys that have local cultural characteristics as a form of early childhood introduction to their culture as well as a medium for educators to internalize character building. The process of creating educational toys in this paper uses methodological steps that are described in a descriptive qualitative way, starting from data collection, data analysis, and the embodiment process. In this paper, will be described the process of creating educational toys in the form of amigurumi with the theme of Ramayana, represented by the characters Rama and Sinta which visual ideas are based on Kamasan-style puppet paintings and an analysis of their use for early childhood character building. The benefits of using Rama and Sinta amigurumi dolls in learning are: as a visual literacy of local culture for early childhood and as an interesting medium for conveying character building values.